THE LEGAL TERMS FORMED WITH AFFIXES IN THE KARAKALPAK LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The thesis speaks about the study of legal terms in Karakalpak language. Both productive and unproductive use of word-forming affixes were studied.